A rare case of early onset childhood schizophrenia with predominant negative symptoms - Raja, Sravya; Kotturu, Mounika Katyayani; Kandriga, Vamsi Krishna Reddy; Potla, Vamsi Krishna (International Journal of Contemporary Pediatrics, 2022)
Early onset childhood schizophrenia (<13 years) is often a rare disorder with an estimated prevalence of 1 in 30,000 children. The disease is characterized by hallucinations, delusions and cognitive impairments. It tends to present insidiously with a premorbid period of developmental delay or regression with declining academics. Often, the diagnosis of early onset schizophrenia is missed or sometimes misdiagnosed as pervasive developmental disorders. We here present a rare case of 10-year-old boy who showed behavioural abnormalities suggestive of psychosis.